The Effect of Technological Extraction Parameters on the Content of Flavonoids and Extractive Substances in Extracts of an Antidiabetic Herbal Mixture - S. Kholmatov; Kh. M. Kamilov (Scientific Trends, 2025)
The results of experiments studying the influence of technological extraction parameters (temperature, alcohol concentration, time, and hydromodule) on the yield of total flavonoids and extractive substances from an antidiabetic herbal mixture composed of bean pods, fig leaves, chicory roots, and goat’s rue herb are presented. Based on the experimental results, it can be concluded that there is a direct relationship between the technological parameters of the extraction process and the amounts of total flavonoids and extractive substances in the extracts. Under optimal extraction conditions, the total flavonoid yield was about 1.10%, while the yield of total extractive substances was around 15.0%. The quantitative determination of total flavonoids in the extracts was performed spectrophotometrically, recalculated as rutin using aluminum chloride.
Keywords: antidiabetic herbal mixture, extraction, maceration, total flavonoids, antioxidant, glycemic, extractive substances, technological parameters, process.